2005
DOI: 10.1177/1362361305049030
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and imitation deficits from infancy to 4 years of age in children with autism

Abstract: The present study investigated the influence of developmental level on interaction and imitation in infants and young children with autism on the basis of family videos and filmed consultation. The sample comprised 18 children with autism divided into groups according to their developmental quotient (DQ>50 and DQ<50). A quantitative evaluation was performed on video observations at four periods (10-12 months, 16-18 months, 24-26 months, after 4 years) using scales appropriate for the evaluation of interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 28 publications
1
18
0
2
Order By: Relevance
“…Parental reports of these behaviours generally substantiated what was observed, suggesting an overall impairment in the use of smiling and appropriate affect during the infancy period. These findings, once again, accord with previous early development studies (Adrien et al 1991;Receveur et al 2005;Werner et al 2000). Studies have also found that children with autism show odd 'blends' of affect, and less animation in emotional expressions (Clifford et al 2006;Baranek 1999;Loveland et al 1994).…”
Section: Dyadic Behaviourssupporting
confidence: 94%
See 1 more Smart Citation
“…Parental reports of these behaviours generally substantiated what was observed, suggesting an overall impairment in the use of smiling and appropriate affect during the infancy period. These findings, once again, accord with previous early development studies (Adrien et al 1991;Receveur et al 2005;Werner et al 2000). Studies have also found that children with autism show odd 'blends' of affect, and less animation in emotional expressions (Clifford et al 2006;Baranek 1999;Loveland et al 1994).…”
Section: Dyadic Behaviourssupporting
confidence: 94%
“…In a study of videotaped first birthday parties of these same infants, Osterling and Dawson (1994) also revealed early joint attention deficits, whereby the infants with AD showed objects to a social partner less often than typically developing infants, and none demonstrated proto-declarative pointing. Joint attention behaviours of showing objects, alternating gaze, and gaze following have also been found to be problematic for infants with AD in other similar studies (Bernabei et al 1998;Maestro et al 1999;Mars et al 1998;Receveur et al 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Additionally, TgsAPPa mice demonstrate behavioral impairments that simulate autistic behaviors in humans. In addition to impaired social interaction, which is a cardinal autistic behavioral phenotype, patients have also demonstrated hypoactivity (Gillberg and Billstedt, 2000;Maestro et al, 2005;Receveur et al, 2005). TgsAPPa mice exhibit reduced preference for social interaction, indicating impaired sociability ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These preliminary studies, typically limited to examining consonant and syllable profiles within specific populations or subgroups, have aided our understanding of children with typical speech sound development, at high risk for speech-language disorder (Oller, Eilers, Neal, & Schwartz, 1999), Down's syndrome (Smith & Oller, 1981), and hearing impairment (Ertmer et al, 2002;Ertmer & Mellon, 2001;Ertmer, Kloiber, Jung, Kirleis, & Bradford, 2012). Although initially descriptive in nature, small-scale single subgroup studies provide important direction for larger comparative studies within heterogeneous populations (Receveur et al, 2005).…”
Section: Introductionmentioning
confidence: 97%